Advances in non-contrast quiescent-interval slice-selective (QISS) magnetic resonance angiography. Issue 1 (January 2019) - Edelman, R.R.; Carr, M.; Koktzoglou, I.
Abstract : There is a pressing clinical need to develop accurate, efficient non-contrast magnetic resonance angiography (NC-MRA) techniques. Our efforts in the field have focused on a novel non-subtractive technique called quiescent-interval slice-selective (QISS) MRA. Compared with other NC-MRA techniques, QISS has the advantage of being more accurate while enabling a simpler and more efficient workflow. The original implementation, which uses electrocardiogram (ECG) gating and a Cartesian k-space trajectory, is a reliable technique for the evaluation of peripheral arterial disease (PAD). Recent advances in QISS technology include the use of a radial k-space trajectory, which facilitates rapid imaging of the coronary, renal, and pulmonary arteries as well as other vascular beds, and ungated ("UnQISS") acquisitions for PAD.